Answer:
to simplify the square root of 75, first I recognize that the perfect square 25 goes into it. So 75 = 25 x 3. Therefore the square root of 75 equals the square root of 25 times the square root of 3. And that means just 5 times the square root of 3.
Step-by-step explanation:
The 2nd one. Elsa should subtract the numerators instead of adding them carson’s pumpkin weighs 1/4 pound
Answer: x = -0.377
Step-by-step explanation:
We have the equation:
4^(5*x) = 3^(x - 2)
Now we can use the fact that:
Ln(A^x) = x*Ln(A)
Then we can apply Ln(.) to both sides of the equation to get:
Ln(4^(5*x)) = Ln(3^(x - 2))
(5*x)*Ln(4) = (x - 2)*Ln(3)
(5*x)*Ln(4) - x*Ln(3) = -2*Ln(3)
x*(5*Ln(4) - Ln(3)) = -2*Ln(3)
x = -2*Ln(3)/(5*Ln(4) - Ln(3)) = -0.377
Answer:Bill
Step-by-step explanation:
Because Bill scored to the nearest 100